Vitamin D status and its correlates in Saudi male population - Karim H. Farhat; Mostafa A. Arafa; Danny M. Rabah; Hussein S. Amin; Nahla K. Ibrahim (BMC, 2019)
Abstract Background Vitamin-D deficiency is a universal health problem caused primarily by inadequate exposure to sunlight. This study aimed to assess the vitamin D status and investigate the factors affecting vitamin D distribution among Saudi males. Methods A cross-sectional study was conducted at the King Saud University Medical City from December 2015 to August 2016. Saudi males attending the outpatient primary health care clinics were invited to participate in the study. Data were collected on the current and past health status along with biochemical investigations for total 25-hydroxyvitamin D (25OHD), blood sugar, and cholesterol. Results Majority of the participants (76.1%) had vitamin D deficiency. Blood sugar level, age, and cholesterol level were the most significant factors associated with vitamin D status. The highest percentage of deficiency was observed in the youngest age group (30-40 years). With increasing age, the percentage of deficiency decreased significantly. Those with normal blood sugar and cholesterol level had higher serum vitamin D levels compared to those with diabetes and hypercholesterolemia. Conclusions Vitamin D deficiency is still endemic in Saudi Arabia, particularly among younger males and those with diabetes and hypercholesterolemia. Vitamin D screening, supplementations, and vitamin D-fortified foods should be provided especially for these groups.